ACUTE ORAL TOXICITY STUDY OF ARECA CATECHU LINN. AQUEOUS EXTRACT IN SPRAGUE DAWLEY RATS - Meutia Sari, Liza; Suyatna, FD; Utami, Sri; Chairul, .; Subita, Gus Permana (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Areca catechu Linn. (A. catechu L.), commonly known as biji pinangâ€ by the locals, belongs to botanical family Palmaceae. This plant is traditionally used in Indonesia as traditional ceremonial cultural role. The evaluation of toxic properties of A. catechu L. is crucial considering that this nut is one of predisposing factor in aetiology of oral cancer and its exposure may cause undesirable effect on health. Hence, this study, the acute oral toxicity of A. catechu L. nuts extract was investigated in rats, as per OECD Guidelines 423 for acute protocols. The body weight, possibility of death, and activity parameters were measured for 14 days to ascertain the median lethal dose (LD50) of the extract. At the end of the study, all the animals were sacrified. The LD50 was found to be more than 15.000 mg/kg body weight in the treated group. There was significant weight increase (p<0,05). No mortality was observed during the course of whole 14 days study period. No detectable alterations were found in activity parameter in treated group when compared to control group. Overall, the results suggest that oral administration of aqueous extract of A. catechu L. did not produce any significant toxic effect in rats. Keywords: Areca catechu Linn., Acute Oral Toxicity, Lethality (LD50)